2015
DOI: 10.1016/j.jpainsymman.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation of the Edmonton Symptom Assessment System in Chinese Patients

Abstract: The C-ESAS is a good tool for measuring multidimensional symptoms in Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…On the DT, participants evaluate an average week level of distress, whereas they report on a day level on the ESAS-r. As a consequence, higher sensitivity or lower stability is expected on the ESAS-r. The ESAS was originally designed to be used twice a day [ 12 ] and most studies investigating its stability have selected hours to days intervals [ 21 23 , 44 46 ]. This stresses the fact that lower stability over longer periods of time for such an instrument is a sought-after property as it may reflect sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…On the DT, participants evaluate an average week level of distress, whereas they report on a day level on the ESAS-r. As a consequence, higher sensitivity or lower stability is expected on the ESAS-r. The ESAS was originally designed to be used twice a day [ 12 ] and most studies investigating its stability have selected hours to days intervals [ 21 23 , 44 46 ]. This stresses the fact that lower stability over longer periods of time for such an instrument is a sought-after property as it may reflect sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research groups have further validated ESAS both linguistically and psychometrically in Chinese,(26) Flemish,(27) French,(28) German,(29) Icelandic,(30) Italian,(31), Japanese,(32) Korean,(33) Portugese,(35) Spanish,(34) Thai,(36) and Turkish. (37) An Arabic variation of ESAS is also available.…”
Section: B Past Developmentsmentioning
confidence: 99%
“…[ 9 ] Previous studies examining the psychometrics of ESAS also confirmed the one-dimensional model. [ 10 13 14 16 18 ] However, despite the confirming psychometric properties of ESAS, Carvajal et al . used exploratory factor analysis in examining the factor structure of the tool and achieved three dimensions of soft physical, hard physical, and emotional components,[ 13 ] which was different from the one-dimensional factor structure introduced by Bruera et al .…”
Section: Discussion and C Onclusionsmentioning
confidence: 99%
“…[ 13 ] Due to its ease of use, ESAS was quickly used in palliative care and care programs for cancer patients and was adopted by different researchers in Spain, Italy, Thailand, Germany, Switzerland and China. [ 13 14 15 16 17 18 ] Dong et al . for instance evaluated the psychometric properties of ESAS in China and approved its criterion validity, internal consistency, and reliability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation